2017
DOI: 10.1016/j.dld.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of capsule endoscopy versus magnetic resonance enterography and small bowel contrast ultrasound in the evaluation of small bowel Crohn’s disease: Systematic review and meta-analysis

Abstract: CE, MRE and SICUS have similar DY for detection of SB CD in both suspected and established CD. CE is superior to MRE for detection of proximal SB disease, however the risk of capsule retention should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 53 publications
(51 reference statements)
2
73
0
2
Order By: Relevance
“…Therefore, the assessment of small bowel mucosal healing in areas that are beyond the reach of esophagogastroduodenoscopy and ileocolonoscopy should be considered as well. Video capsule endoscopy is effective for assessment of small bowel mucosal healing and may be superior to magnetic resonance enterography in the evaluation of proximal small bowel lesions . The Lewis score and Capsule Endoscopy Crohn's Disease Activity Index have been validated for the assessment of disease activity and mucosal healing using video capsule endoscopy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the assessment of small bowel mucosal healing in areas that are beyond the reach of esophagogastroduodenoscopy and ileocolonoscopy should be considered as well. Video capsule endoscopy is effective for assessment of small bowel mucosal healing and may be superior to magnetic resonance enterography in the evaluation of proximal small bowel lesions . The Lewis score and Capsule Endoscopy Crohn's Disease Activity Index have been validated for the assessment of disease activity and mucosal healing using video capsule endoscopy .…”
Section: Resultsmentioning
confidence: 99%
“…Video capsule endoscopy is effective for assessment of small bowel mucosal healing 111 and may be superior to magnetic resonance enterography in the evaluation of proximal small bowel lesions. 112 The Lewis score and Capsule Endoscopy Crohn's Disease Activity Index have been validated for the assessment of disease activity and mucosal healing using video capsule endoscopy. 113,114 However, the price of video capsule endoscopy is high, so it may be more cost-effective in high-risk patients such as those who have had multiple small bowel resections or with aggressive small bowel disease.…”
Section: Statement 11mentioning
confidence: 99%
“…4 In addition, the program should only be offered to individuals with a substantially increased risk of pancreatic cancer. This was shown in a simulation study by Pandharipande et al, 5 who found that screening of low-risk individuals was associated with a reduced life expectancy, an outcome attributed to the increased discovery of insignificant lesions and subsequent unnecessary surgical intervention.…”
Section: Screening Of Individuals At High Risk For Pancreatic Cancermentioning
confidence: 84%
“…The discrepancy between imaging and CE has been attributed to the low sensitivity of MRE and CTE for luminal inflammation not involving deeper intestinal wall layers. 4,5 However, such CE findings have often been dismissed as clinically irrelevant. In our study we demonstrated that CE findings changed the patient management (ie, initiation or escalation of therapy) in up to 50% of cases.…”
Section: Unexplained Symptoms and Hidden Inflammation In Patients Witmentioning
confidence: 99%
“…A metaanalysis has shown that capsule endoscopy is superior to barium studies, CTE, push enteroscopy, and ileocolonoscopy for detecting recurrent small-bowel CD [57]. In another meta-analysis, however, capsule endoscopy was found to have a diagnostic yield that was similar to MRE and small-intestine contrast US [58]. A recent prospective study showed video CE predicts both short-term and longterm risk of disease exacerbation [59].…”
Section: Capsule Endoscopymentioning
confidence: 99%